EVALUASI DEFECT PRODUK SARUNG ATBM BERBASIS PENDEKATAN GREY FMEA DAN RCA - Olivia, Vina Agustin; Mahbubah, Nina Aini (Fakultas Teknik, Universitas Riau Kepulauan, 2023)
Product quality is a crucial factor in maintaining business continuity by implementing essential processes. The traditional production process of a sarong involves non-machined looms (ATBM), which can lead to defects that reduce the quality of the sarongs. This research aims to evaluate the occurrence of defects throughout the ATBM sarong production process using the Grey-FMEA and RCA approaches. The results of the Grey FMEA method showed that defects occurred in woven sarongs due to the sheath-cutting error and color mixing score during the thread dyeing process. The factor causing the defect is the error in cutting long and short woven sarongs differently due to a mismatch in the pattern of the woven sarong. Therefore, the proposed improvement is that artisans should concentrate on making woven sarongs. Analysis of the causes of sheath defects in the color mixing process during the yarn dyeing process found that poor quality paint and yarn affected the process of dye absorption into the yarn. The proposed improvement includes quality dye and thread raw materials that should be provided so that quality products will be produced.